Long-term survival and undetectable circulating tumor DNA following comprehensive involved site radiotherapy for oligometastases - Rachel Radigan; Caleb S. Kao; Michael Krainock; Minetta C. Liu; Vani Gupta; Lauren Alexander; Symeon Missios; John Hsu; Ashish Sangal; Michael T. Milano; Johnny Kao (Scientific Reports)
Abstract Distant metastases account for ~ 90% of cancer deaths and major responses with systemic therapy alone for metastatic cancers are so rare that the National Cancer Institute launched the Exceptional Responders Initiative. Comprehensive involved site radiotherapy (ISRT) is a promising treatment for oligometastases but the role of circulating tumor DNA to confirm durable molecular response following treatment remains unexplored. Among 597 consecutive patients with distant metastases treated with radiation therapy from 2014 to 2021, 133 (22%) were oligometastatic and 464 (78%) were polymetastatic. The 5-year overall survival was 38% for oligometastases vs. 3% for polymetastases (p < 0.001). At a median follow-up of 71 months for treated oligometastases, 37 (28%) exceptional responders (ER) remain alive and recurrence free at ≥ 2 year follow-up. Among ER, 49% underwent stereotactic radiotherapy (median 27 Gy in 3 fractions, EQD2 43 Gy), 65% underwent intensity-modulated radiation therapy (median 53 Gy in 24 fractions, EQD2 54 Gy), and 76% received additional systemic therapy. Although ctDNA testing was not possible in most ER due to patient refusal or tumor specimen quality, all 12 ER tested ctDNA-negative. Long-term complete responses, including molecular complete responses, are achievable with comprehensive ISRT in diverse clinical presentations.